First Investigation of the Marine Gastrotrich Fauna from the Waters of North Tunisia, with the Description of a New Species of Halichaetonotus (Gastrotricha, Chaetonotida) - Aicha Souid; Mehrez Gammoudi; Francesco Saponi; M’hamed El Cafsi; M. Antonio Todaro (Diversity)
Gastrotrichs (hairy bellies) are microscopic, acoelomate worms that live in freshwater and marine environments and represent one of the significant components of the meiobenthic communities. There are over 520 marine species, and several of them are also found in the Mediterranean Sea. However, data on the gastrotrich fauna from Tunisia is negligible, with nearly zero annotated records. We have initiated a series of investigations along the Tunisian shores to address this gap. Herein, we report data from four collecting sites on the northern Tunisian coastline. Sandy samples from 2 m water depth yielded 21 species, 11 in the order Macrodasyida and 10 in Chaetonotida. One chaetonotidan new to science is formally described, while morphometric data and photomicrographs are provided for all the others. Incidentally, we report on the longest gastrotrich ever found. Information about the microhabitat’s characteristics, including the water’s salinity and temperature and granulometric parameters of the sediment, are also reported. Finally, we provide information on Tunisian species previously discovered by our team and involved in phylogenetic studies for which morphological data and details about their findings have never been published. We explicitly address and correct the errors in GenBank concerning the attribution of gene sequences for these species.